ANALISIS PENDEKATAN SISTEM TERHADAP PRESTASI BELAJAR SISWA DI SEKOLAH MAS MUALLIMIN UNIVA - Dian Pratiwi Br. Marpaung; Rama Satya Tanjung; Ella Nurmaini; Lucky Tirta Nurarfiansyah; Maulidayani (JOURNAL SAINS STUDENT RESEARCH, 2023)
This mini-research aims to evaluate the positive influence of the systems approach on student learning achievement at the Mas Muallimin UNIVA School. Through a pre-test post-test control group experimental design, students were divided into two groups: the experimental group with learning using a systems approach, and the control group with conventional learning. The type of research used by researchers is field research. Meanwhile, the approach used in this research is a qualitative descriptive approach. The results of the research show that the systems approach is a step-by-step procedure used in solving business problems or efforts to solve problems which are carried out by looking at existing problems as a whole and carrying out system analysis. So, a systems approach is a perspective or way of thinking using system concepts in solving a problem.